Pax6 Downregulation Mediates Abnormal Lineage Commitment of the Ocular Surface Epithelium in Aqueous-Deficient Dry Eye Disease - Chen, Ying Ting; Chen, Feeling Y. T.; Vijmasi, Trinka; Stephens, Denise N.; Gallup, Marianne; McNamara, Nancy A. (PloS one, 2013)
Keratinizing squamous metaplasia (SQM) of the ocular surface is a blinding consequence of systemic autoimmune disease and there is no cure. Ocular SQM is traditionally viewed as an adaptive tissue response during chronic keratoconjunctivitis sicca (KCS) that provokes pathological keratinization of the corneal epithelium and fibrosis of the corneal stroma. Recently, we established the autoimmune regulator-knockout (Aire KO) mouse as a model of autoimmune KCS and identified an essential role for autoreactive CD4+ T cells in SQM pathogenesis. In subsequent studies, we noted the down-regulation of paired box gene 6 (Pax6) in both human patients with chronic KCS associated with Sjögren's syndrome and Aire KO mice. Pax6 encodes a pleiotropic transcription factor guiding eye morphogenesis during development. While the postnatal function of Pax6 is largely unknown, we hypothesized that its role in maintaining ocular surface homeostasis was disrupted in the inflamed eye and that loss of Pax6 played a functional role in the initiation and progression of SQM. Adoptive transfer of autoreactive T cells from Aire KO mice to immunodeficient recipients confirmed CD4+ T cells as the principal downstream effectors promoting Pax6 downregulation in Aire KO mice. CD4+ T cells required local signaling via Interleukin-1 receptor (IL-1R1) to provoke Pax6 loss, which prompted a switch from corneal-specific cytokeratin, CK12, to epidermal-specific CK10. The functional role of Pax6 loss in SQM pathogenesis was indicated by the reversal of SQM and restoration of ocular surface homeostasis following forced expression of Pax6 in corneal epithelial cells using adenovirus. Thus, tissue-restricted restoration of Pax6 prevented aberrant epidermal-lineage commitment suggesting adjuvant Pax6 gene therapy may represent a novel therapeutic approach to prevent SQM in patients with chronic inflammatory diseases of the ocular surface.